PRINSIP-PRINSIP KESOPANAN DALAM FILM THE HELP KARYA TATE TAYLOR : SUATU ANALISIS PRAGMATIK - MAKATITA, JENIFFER LITSIA ISABELLA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT This research entitled ‘Prinsip-prinsip Kesopanan dalam Film The Help Karya Tate Taylor : Suatu Analisis Pragmatik’ focuses on maxim related to the politeness principles. The aims of this research is to identify, classify and analyze the politeness principles and their function in The Help movie.This research used a descriptive method. The data collected from conversation among characters, then classify and analyze them according to the concept of Leech (1983). The result shows that there are six maxims of politeness and their function applied by the characters in their dialogues. First, tact maxim consist of 17 utterances functioning to minimizes cost to other and maximizes benefit to the other. Second, generosity maxim consist of 11 utterances functioning to minimizes benefit to self and maximizes cost to self. Third, approbation maxim consist of 21 utterances functioning to minimizes dispraise of other and maximizes praise of other. Fourth, modesty maxim consist of 9 utterances functioning to minimizes praise of self and maximizes dispraise of self. Fifth, agreement maxim consist of 10 utterances functioning to maximizes agreement between self and other and minimizes disagreement between self and other. Sixth, sympathy maxim consist of 9 utterances functioning to minimizes antipathy between self and other and maximizes sympathy between self and other. It is expected that this research will help students and readers in learning pragmatic aspects, especially about politeness principles. Keywords : Politeness Principles, Maxims, Pragmatic Analysis, The Help Movie